A Clinical Trial with Combined Transcranial Direct Current Stimulation and Attentional Bias Modification in Alcohol‐Dependent Patients - den Uyl, Tess E. (Alcohol Clin Exp Res, 2018)
BACKGROUND: Modifying attentional processes with attentional bias modification (ABM) might be a relevant add‐on to treatment in addiction. This study investigated whether influencing cortical plasticity with transcranial direct current stimulation (tDCS) could increase training effects. tDCS could also help alcohol‐dependent patients to overcome craving and reduce relapse, independent of training. These approaches were combined to investigate effects in the treatment of alcoholism. METHODS: Ninety‐eight patients (analytical sample = 83) were randomly assigned to 4 groups in a 2‐by‐2 factorial design. Patients received 4 sessions of ABM (control or real training) combined with 2 mA tDCS (active: 20 minutes or sham: 30 seconds) over the left dorsolateral prefrontal cortex. Alcohol bias and craving were assessed, and treatment outcome was measured as relapse after 1 year. RESULTS: Attentional bias scores indicated that during the training only the group with active tDCS and real ABM displayed an overall avoidance bias (p < 0.05). From pre‐ to postassessment, there were no main or interaction effects of tDCS and ABM on the bias scores, craving, or relapse (p > 0.2). However, effects on relapse after active tDCS were in the expected direction. CONCLUSIONS: There was no evidence of a beneficial effect of tDCS or ABM or the combination. Whether the absence of effect was due to issues with the outcome measurements (e.g., lack of craving, high dropout, and unreliable measurements) or aspects of the intervention should be further investigated.